The Effect of Content Marketing and Influencer Marketing on Purchase Intention for Luxcrime Products on the Tiktok Application in Surabaya - Diba, Adinda Farah; Aminah, Siti (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Amidst the rapid advancements in the digital era, social media marketing strategies have become readily accessible. Capitalizing on trending social media platforms like TikTok to attract consumer interest is achieved through content marketing and influencer marketing strategies. This research aims to investigate the influence of Content and Influencer Marketing on Purchase Intention, employing Luxcrime products in Surabaya as the research subject. The population of this study encompasses TikTok users who have encountered content marketing featuring influencers on Luxcrime's account. The sample size comprises 90 respondents from the city of Surabaya. Data analysis was conducted using the SEMPLS method with SmartPLS software. This quantitative research employed PLS analysis. The research concludes that Content Marketing and Influencer Marketing effectively generate purchase intention for Luxcrime products in Surabaya.